(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2015)
In this study, treatment of phosphogypsum (PG) with lime-water (LWT), sulphuric acid (SAT), a mixture of H2SO4 and HNO3 (AWT), PG-water (ST), and PG-limestone (LT) was attempted to purify PG and improve its quality so that it can be used for manufacture of ordinary Portland Cement (OPC). The treatment of PG removes P2O5, SO3, and MgO impurities into water-leachable phase. Chemical analysis of the treated PG and mechanical properties of OPC mortar after various treatment of PG established improvement of the quality of PG. The purified PG contain less impurities when compared with untreated PG. It was observed that the leachable of P2O5, SO3, and MgO in these samples ranged from 86% to 90%, 69% to 94%, 96% to 99%, respectively, can be achieved using these treatment processes. The major phases Alite (C3S), Belite (C2S), Aluminatetricalcic(C3A), and Tetra-calcium aluminoferrite (C4AF), and control ratios Lime Saturation factor (LSF), Aluminum/Iron ratio (AR), and Silica ratio (SR) were measured. These experimental results showed that the C3S, C3A and C4AF, C2S, LSF, AR, and SR contents fulfilled the requirement of the Jordan Standards and European Standards; hence treated PG can be replaced by natural gypsum. The X-ray diffraction analysis of OPC samples showed that C3S and C2S are major mineral phases, C3A and C4AF represent as minor constituents while the CaO and MgO represent as trace phases. The effect of treated PG on the mechanical properties of OPC mortar was investigated. The OPC produced with purified phosphogypsum were found to have strength properties similar to those produced from mineral gypsum thus fulfilling Jordan Standards and European Standards. The present study indicates that the use of PG in OPC manufacture can solve the waste disposal problem thus cleaning our environment at one hand, on the other hand it can save natural raw materials i.e gypsum. Bangladesh J. Sci. Ind. Res. 50(4), 241-250, 2015